PA-NI DINGIR-LIMGIŠDAG-TI(sic) = tar-ša-an-zi-pí pé-ra-an? Randnotizen zu CTH 652 - Groddek, Detlev (2012)
The present paper focusses on some details of a text group recently discussed in this journal by Š. Velhartická. First, her newly proposed equation of PA-NI DINGIR- LIM GIŠ DAG- TI (sic) with taršanzipi peran is shown to be erroneous. Second, it is suggested that the small group of texts KBo 41.35 with duplicates KBo 41.36 and KBo 41.37 be added to CTH 652 due to the clearly identical and otherwise rarely used cultic paraphernalia in both groups. By doing so the person of the author is ascertained in the Hittite king Ḫattušili III, and it is argued that the use of Hattic recitations in the freshly composed text may stem from the background of the regained city of Nerik and its cult of Hattic origin.
Keywords: Nerik; Ḫattušili III; Man of the Stormgod; Hittite